Quantitative models as an aid to development assistance policy - Organization for Economic Cooperation and Development (Paris : Organisation for Economic Cooperation and Development, 1967)
This is a report of an expert group set up by the working party on assistance requirements of the OECD. It attempts to assess the methods by which estimated have been made of the assistance requirement of less developed countries.
Includes bibliographical references: p. 73-78.
lje 18/05/2018
Loans
Keywords: Economic development; Economic development--Mathematical models; Developing countries